Coping strategies in individuals at risk and not at risk of mobile phone addiction - Dziurzyńska, Ewa; Pawłowska, Beata; Potembska, Emilia (Current Problems of Psychiatry, 2017)
The aim of the present study was to provide an answer to the question of whether, and what, differences in stress coping strategies could be found between university students at risk and those not at risk of mobile phone addiction. The study included 408 students aged 19 to 28 years. The following instruments were used: a sociodemographic questionnaire, the Mobile Phone Addiction Assessment Questionnaire (in Polish, Kwestionariusz do Badania Uzależnienia od Telefonu Komórkowego, KBUTK) by Pawłowska and Potembska, and the Coping with Stress Questionnaire (SVF) by Janke, Erdmann, and Boucsein, translated into Polish by Januszewska. The results of the study showed that individuals at risk of mobile phone addiction were more likely to cope with stress by seeking substitute gratification, reacting with resignation, passivity, dejection and hopelessness, blaming themselves, pitying themselves and looking for support. They also tended to ruminate over their suffering, withdraw from social interactions, react with aggression and/or take to drinking.